Pemanfaatan Limbah Styrofoam Sebagai Bahan Tambah Campuran AC-BC Yang Menggunakan Sungai Bittuang - Nelmayanti Sambo; Rais Rachman; Alpius (Paulus Civil Engineering Journal, 2021)
This study was intended to determine the characteristics of the mixture of intermediate layers of concrete with the addition of styrofoam waste in the mixture of intermediate layers of concrete. The composition of the mixture of intermediate lasts and Marshall test to get the characteristics of the mixture of intermediate layers of concrete with the addition of straw ash Styrofoam waste as a cement filler substitution. The results of testing the characteristics of the Asphalt Concrete – Binder Course (AC-BC) mixture using Styrofoam waste added material through the Conventional Marshall test, namely if the Styrofoam waste content is 1%, then the VIM, VMA, and Flow values decrease at each Styrofoam waste level, while for Stability and VFB values always increase at each level of Styrofoam waste. The Marshall Immersion test results obtained a Stability value of the mixture that could withstand Immersion for 24 hours.